2014
DOI: 10.1590/s0044-59672014000200010
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive aspects of Macrobrachium amazonicum (Decapoda: Palaemonidae) in the State of Amapá, Amazon River mouth

Abstract: Macrobrachium amazonicum is an indigenous prawn vastly distributed in basins of South America, widely exploited by artisanal fisheries in northern and northeastern Brazil and, with great potential for aquaculture. This study aimed to investigate general aspects of population structure and reproductive characteristics (size at first maturity, fecundity and reproductive output) of M. amazonicum from two important areas to artisanal prawn fishing located at the mouth of the Amazon River, State of Amapá. The speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
28
2
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 25 publications
8
28
2
10
Order By: Relevance
“…The occurrence of morphotype differences in populations of Macrobrachium from inland streams, as reported here, is uncommon. These environments have lower food availability than estuaries and larger rivers (Chanton & Lewis, ; González‐Gordillo & Rodrigues, ), where multiple morphotypes have commonly been recorded in M. amazonicum (Freire et al, ; Lima et al, ; Silva et al, ). In general, prawn species from inland streams, such as M. brasiliense , have an abbreviated larval development (Anger, ; Jalihal, Sankolli, & Shenoy, ), which is an adaptation to low nutrient availability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The occurrence of morphotype differences in populations of Macrobrachium from inland streams, as reported here, is uncommon. These environments have lower food availability than estuaries and larger rivers (Chanton & Lewis, ; González‐Gordillo & Rodrigues, ), where multiple morphotypes have commonly been recorded in M. amazonicum (Freire et al, ; Lima et al, ; Silva et al, ). In general, prawn species from inland streams, such as M. brasiliense , have an abbreviated larval development (Anger, ; Jalihal, Sankolli, & Shenoy, ), which is an adaptation to low nutrient availability.…”
Section: Discussionmentioning
confidence: 99%
“…Taking M. amazonicum as an example, several studies were made after the description of morphotypes (Moraes- Riodades & Valenti, 2004), and reported the presence or absence of multiple morphotypes, depending on the population. Among the studies that found multiple morphotypes in M. amazonicum, many addressed estuarine populations (Flexa, Silva, & Cintra, 2005;Freire, Bentes, Fontes, & Silva, 2017;Freire, Marques, & Silva, 2012;Lima et al, 2014;Lucena-Fredou, Rosa Filho, Silva, & Azevedo, 2010;Santos, Sampaio, & Soares-Filho, 2006;Silva et al, 2019) and fewer addressed populations from inland rivers (Pantaleão et al, 2014;Vergamini, Pileggi, & Mantelatto, 2011).…”
Section: Species Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…No estuário amazônico, há uma leve predominância de fêmeas na população, principalmente no período reprodutivo (LIMA, 2014). Para fêmeas de M. amazonicum cultivadas na Colômbia, Aya-Baquero e Velasco-Santamaría (2013) descreveram comprimento total variando de 4,0 a 5,8 centímetros.…”
Section: Discussionunclassified
“…Para fêmeas de M. amazonicum cultivadas na Colômbia, Aya-Baquero e Velasco-Santamaría (2013) descreveram comprimento total variando de 4,0 a 5,8 centímetros. Porém, na natureza há registro de indivíduos capturados medindo com 15 centímetros de comprimento total (LIMA, 2014). No nordeste do Brasil, há registro de capturas de animais com comprimento entre 4,5 e 10,5 centímetros (SAMPAIO et al, 2007).…”
Section: Discussionunclassified